Лесные сказки - Притулина Надежда Петровна (Серия "Коллекция любимых сказок", 2016)
Экземпляры: Ф1, ф2, ф3, ф4, ф5, ф6, ф7, ф31, ф32, ВО (20171101) / Инвентарный номер: 54896 / Цена: 62.00 / Сис.шифр: Д / Авт.знак: П 77 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6